Data Management Practices and Perspectives of Atmospheric Scientists and Engineering Faculty. - Christie Wiley; William H. Mischo (Issues in Science and Technology Librarianship, 2016)
This article analyzes 21 in-depth interviews of engineering and atmospheric science faculty at the University of Illinois Urbana-Champaign (UIUC) to determine faculty data management practices and needs within the context of their research activities. A detailed literature review of previous large-scale and institutional surveys and interviews revealed that researchers have a broad awareness of data-sharing mandates of federal agencies and journal publishers and a growing acceptance, with some concerns, of the value of data-sharing. However, the disciplinary differences in data management needs are significant and represent a set of challenges for libraries in setting up consistent and successful services. In addition, faculty have not yet significantly changed their data management practices to conform with the mandates. The interviews focused on current research projects and funding sources, data types and format, the use of disciplinary and institutional repositories, data-sharing, their awareness of university library data management and preservation services, funding agency review panel experiences, and struggles or challenges with managing research data. In general, the interviews corroborated the trends identified in the literature. One clear observation from the interviews was that scientists and engineers take a holistic view of the research lifecycle and treat data as one of many elements in the scholarly communication workflow. Data generation, usage, storage, and sharing are an integrated aspect of a larger scholarly workflow, and are not necessarily treated as a separate entity. Acknowledging this will allow libraries to develop programs that better integrate data management support into scholarly communication instruction and training. [ABSTRACT FROM AUTHOR]